Classifying winning performances in international women`s rugby union - Scott, G. A.; Edwards, O.; Bezodis, N. E.; Waldron, M.; Roberts, E.; Pyne, D. B.; Mara, J.; Cook, C.; Mason, L.; Brown, M. R.; Kilduff, L. P. (International Journal of Sports Physiology and Performance, 2023)
Purpose: The efficacy of isolated and relative performance indicators (PIs) has been compared in rugby union; the latter more effective at discerning match outcomes. However, this methodology has not been applied in women`s rugby. The aim of this study was to identify PIs that maximize prediction accuracy of match outcome, from isolated and relative data sets, in women`s rugby union.